Low-Dose Antibiotic Prophylaxis Induces Rapid Modifications of the Gut Microbiota in Infants With Vesicoureteral Reflux - William Morello; Federica D'Amico; Jessica Serafinelli; Silvia Turroni; Isabella Abati; Jessica Fiori; Esra Baskin; Fatos Yalcinkaya; Augustina Jankauskiene; Marco Pennesi; Aleksandra Zurowska; Francesca Becherucci; et al. (Frontiers in Pediatrics, 2021)
Background and Objectives: Maturation of the gut microbiota (GM) in infants is critically affected by environmental factors, with potential long-lasting clinical consequences. Continuous low-dose antibiotic prophylaxis (CAP) is the standard of care for children with vesicoureteral reflux (VUR), in order to prevent recurrent urinary tract infections. We aimed to assess short-term GM modifications induced by CAP in infants.Methods: We analyzed the GM structure in 87 infants (aged 1-5 months) with high-grade VUR, previously exposed or naïve to CAP. Microbial DNA was extracted from stool samples. GM profiling was achieved by 16S rRNA gene-based next-generation sequencing. Fecal levels of short- and branched-chain fatty acids were also assessed.Results: 36/87 patients had been taking daily CAP for a median time of 47 days, while 51/87 had not. In all patients, the GM was predominantly composed by Bifidobacteriaceae and Enterobacteriaceae. Subgroup comparative analysis revealed alterations in the GM composition of CAP-exposed infants at phylum, family and genus level. CAP-exposed GM was enriched in members of Enterobacteriaceae and Bacteroidetes, especially in the genera Bacteroides and Parabacteroides, and showed a trend toward increased Klebsiella, often associated with antibiotic resistance. In contrast, the GM of non-CAP children was mostly enriched in Bifidobacterium. No differences were found in fatty acid levels.Conclusions: In infants with VUR, even a short exposure to CAP definitely alters the GM composition, with increased relative abundance of opportunistic pathogens and decreased proportions of health-promoting taxa. Early low-dose antibiotic exposure might bear potential long-term clinical risks.